The Effect Of Company Strategies On The Value Of Manufacturing Companies Listed On The Indonesia Stock Exchange In 2018 – 2021 - Soni Angga; Said Kelana Asnawi; Hendrian Hendrian (PT Mattawang Mediatama Solution, 2023)
The problem faced by companies is the use of debt that has been planned not according to plan, in fact many companies actually use debt excessively. The purpose of this research is to find out whether debt policy affects company value. This research was conducted at manufacturing sector companies listed on the Indonesia Stock Exchange in 2018–2021 with a population of 195 companies, the sample used was 75 companies for four years. Thus, the number of samples used in this study was 300. The variable firm value is proxied by (PBV) while the independent variables in this study are debt policy which is proxied (DER and DER2), investment decisions (KI), profitability (ROE), institutional ownership (INST) and economic conditions (KE). The data analysis method used multiple linear regression with SPSS version 26 software. The results showed that the debt policy variable (DER) had a positive and not significant effect on firm value (PBV), and the non-linear effect of debt policy (DER2) had a positive and not significant effect to firm value (PBV). The investment decision variable (IC) has a positive and significant effect on firm value (PBV). The profitability variable (ROE) has a positive and significant effect on firm value (PBV). The institutional ownership variable (INST) has a positive and insignificant effect on firm value (PBV), and the economic condition variable (KE) has a non positive and insignificant effect on firm value (PBV).